1998
DOI: 10.1101/gad.12.10.1495
|View full text |Cite
|
Sign up to set email alerts
|

Exit from mitosis inDrosophila syncytial embryos requires proteolysis and cyclin degradation, and is associated with localized dephosphorylation

Abstract: The cyclin proteolysis that accompanies the exit from mitosis in diverse systems appears to be essential for restoration of interphase. The early syncytial divisions of Drosophila embryos, however, occur without detectable oscillations in the total cyclin level or Cdk1 activity. Nonetheless, we found that injection of an established inhibitor of cyclin proteolysis, a cyclin B amino-terminal peptide, prevents exit from mitosis in syncytial embryos. Similarly, injection of a version of Drosophila cyclin B that i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

14
127
0
1

Year Published

1998
1998
2015
2015

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 142 publications
(142 citation statements)
references
References 44 publications
14
127
0
1
Order By: Relevance
“…S6a-d). A similar result was reported in drosophila syncitial embryos 10 . Second, we analyzed another Aurora B substrate, MCAK Ser-196 7 .…”
supporting
confidence: 76%
“…S6a-d). A similar result was reported in drosophila syncitial embryos 10 . Second, we analyzed another Aurora B substrate, MCAK Ser-196 7 .…”
supporting
confidence: 76%
“…The activity of APC-Cdc20 appears to be regulated in a partially cell cycle-dependent manner (Su et al, 1998). In the present study, HSF1 was found to interact directly with Cdc20, and this interaction appeared to be responsible for aneuploidy production by HSF1, because transfection of a regulatory domain-deficient HSF1 mutant, which could not bind to Cdc20, also failed to produce aneuploidy in RIF cells (Figure 4).…”
Section: Discussionsupporting
confidence: 50%
“…Characteristically, these early cycles have only S and M phases (Murray and Hunt 1993). Both biochemical and morphological studies have documented that sequential activation and inactivation of Cdk1-CycB play a major role in regulating these biphasic cycles (Edgar et al 1994(Edgar et al , 1995Su et al 1998;Ji et al 2004).…”
Section: E Mbryonic Development Except In Mammals Ismentioning
confidence: 99%